Effects of Activities of Daily Living on Life Satisfaction: The Moderated Mediating Effect of Social Participation by Disability Type - Nagyeong Kim; Youngshin Song (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to examine the effects of activities of daily living (ADL) on life satisfaction among adults with disabilities, focusing on the mediating role of social participation and the moderated mediation effect of disability type. Methods: Data from the 2023 National Survey of Persons with Disabilities were analyzed. Descriptive statistics and correlation analysis were performed using weighted data (N=2,549,155), while the research model was tested using an unweighted sample (n=7,630) via PROCESS Macro Models 4 and 14. Age was included as a covariate to ensure the robustness of the model. Disability types were categorized into external physical, internal physical, and developmental/mental disabilities. Results: ADL had a significant positive total effect on life satisfaction (B=0.36, β=.32, p